Process intensification characteristics of a microreactor absorber for enhanced CO2 capture. (15th January 2016) - Ganapathy, Harish; Steinmayer, Sascha; Shooshtari, Amir; Dessiatoun, Serguei; Ohadi, Michael M.; Alshehhi, Mohamed
Highlights: Enhanced gas separation/CO2 capture using aqueous DEA in micro-structured absorber. 15 straight parallel channels with hydraulic diameter of 456 μm. Achieved close to 100% absorption efficiency under certain operating conditions. Mass transfer coefficients 1–3 orders of magnitude higher than conventional absorbers. Substantial intensification of absorption process achievable using microreactors. Abstract: Gas separation processes, including post-combustion carbon capture (PCCC) by chemical absorption using liquid solvents can be substantially enhanced using high performance micro-structured surfaces to enhance the surface area available for reaction. The present paper studies the hydrodynamics and mass transfer performance of gas–liquid absorption of CO2 into aqueous diethanolamine in a micro-structured reactor. The system was designed to comprise 15 straight parallel channels in a cross flow inlet configuration. The hydraulic diameter of each channel was 456 μm. The performance of the reactor was studied with respect to the absorption efficiency, mass transfer coefficient, acid gas loading ratio, and pressure drop. A flow pattern map was developed using available regime transition criteria. Parametric studies varying the gas and liquid flow rates, as well as their respective concentrations at the reactor inlet, were conducted. The two-phase pressure drop was compared against the predictions of a piecewise model and a reasonably good agreement was obtained. Absorption efficiencies close to 100% were observed under certain operating conditions. The presently achieved values of liquid-side volumetric mass transfer coefficients were between 1–3 orders of magnitude higher than those reported for most conventional gas–liquid absorption systems, which can be attributed to the inherent high specific interfacial area provided through micro-structured surfaces. The results reported here indicate the substantial levels of process intensification that can be achieved using microreactors.